Impact of fire on mechanical properties of concrete containing marble waste - D. Kore Sudarshan; A.K. Vyas (Journal of King Saud University: Engineering Sciences)
Concrete mixes with 75% fraction of coarse aggregate obtained from marble mining waste and 25% with conventional coarse aggregate were designed by particle packing density approach. The variations in mechanical properties of concrete exposed to real standard fire were investigated in a temperature range of 200–800 °C. Properties like compressive strength, ultra-sonic pulse velocity values, loss of mass in concrete specimens did not show any adverse impact at elevated temperature up to 400 °C. Water absorption in marble concrete mixes was less than that of control mixes. In all it was concluded that the mechanical properties of concrete mixes produced from marble waste were found to be satisfactory after fire exposure up to 400 °C. Concrete started deteriorating increase in temperature beyond this value. Keywords: Concrete, Marble waste, Fire, Mechanical properties